Tipping the (Im)balance: Capital inflows, financial market structure, and banking crises. (19th September 2017) - Copelovitch, Mark; Singer, David A.
Abstract: An emerging consensus among scholars and policy‐makers identifies foreign capital inflows as one of the primary determinants of banking crises in developed countries. We challenge this view by arguing that external imbalances are destabilizing only when banks face substantial competition from securities markets in the process of financial intermediation. We assemble a dataset of banking crises covering the advanced industrialized countries from 1976 to 2011 and find evidence of a conditional relationship between capital inflows, a well‐developed securities market, and the incidence of banking crises. We further explore the impact of capital inflows on banks' actual risk taking as indicated by their capital adequacy levels and measures of insolvency risk. Our results demonstrate that prudential capital cushions tend to decline with the combination of capital inflows and prominent securities markets. We highlight the political decisions—often made during the early days of a country's financial development—that determine the relative prominence of banks vs. non‐bank financial institutions and conclude with policy recommendations.